NUTRITIONAL VALUE, SECONDARY METABOLITES, ANTIOXIDANT, ANTI-INFLAMMATORY AND ANTIBACTERIAL ACTIVITIES OF THREE WOODY FORAGE PLANTS - Shu-Wei Zhang; Hui-Fang Shi; Yi Xi; Li Zhang (Journal of Animal and Plant Sciences, 2024)
Thirty-six leaf samples of Sophora davidii, Indigofera amblyantha, and Broussonetia papyrifera were collected during different growth periods. The dynamic changes in nutritional components and secondary metabolites were analysed, and the biological activities of the secondary metabolites were evaluated. The optimal utilization stage of each plant was comprehensively determined. The results showed that S. davidii (the crude protein (CP) content 24.82%, relative feed value (RFV) 186.52)andI.amblyantha (CP 24.28%, RFV 177.54) were premium forage materials and that B. papyrifera (CP 21.65%, RFV 133.84) was a first-level forage. The best period for using the leaves of these three plants as animal feed was the flowering stage. As the growth progressed, the contents of CP, crude fibre (CF), dry matter (DM), and nitrogen-free extract (NFE) decreased, while the CF, neutral detergent fibre (NDF), acid detergent fibre (ADF), and crude ash (Ash) increased. The S. davidii,I. amblyantha, and B. papyrifera contains total flavonoid (0.36-0.70, 1.07-2.87, and 0.59-0.78 mg/g, respectively), tannin (5526.21-7717.77, 4284.03-5818.73, and 6390.66-7640.60 nmol/g, respectively), total phenol (205.62-298.69, 163.22-214.22, and 143.87-214.34 mg/g, respectively), total saponin (0.11-0.22, 0.20-0.39, and 0.10-0.16 ng/g, respectively) and total alkaloid (0.20-0.32, 0.23-0.38, and 0.20-0.36 ng/g, respectively). Moreover, the tannins, total phenols, saponins, flavonoids, and alkaloids in these woody forages scavenged hydroxyl radicals and superoxide anions to varying degrees, and their ability to reduce Fe3+ gradually increased with concentration. These plants inhibited hyaluronidase and albumin denaturation. The alkaloid and flavonoid extracts of S. davidii significantly (P≤0.05) inhibited Staphylococcus aureus with antibacterial diameters of 14.48 and 14.44 mm, respectively. The flavonoid (11.29 mm) and tannin (11.17 mm) extracts of S. davidii significantly (P≤0.05) inhibited Escherichia coli. The alkaloid (12.29 mm) and tannin (13.15 mm) extracts of B. papyrifera, and the flavonoid extract of S. davidii (13.44 mm) and I. amblyantha (10.32 mm) inhibited Bacillus subtilis. The secondary metabolites of these plants possess antioxidant, anti-inflammatory and antibacterial activities. In conclusion, these findings provide new perspectives on the nutritional value and biochemical characteristics of leaves of S. davidii, I. amblyantha, and B. papyrifera, emphasizing their use as valuable feed source for ruminants.
Keywords: biological activity; secondary metabolite; Broussonetia papyrifera; Indigofera amblyantha; Sophora davidii